Estandares de la Calidad del Cuidado de Enfermería y Satisfacción del Usuario Gineco-Obstetricia Hospital Belén de Trujillo-2011 - Pampa Espinoza, Maria Carolina
In order to determine the relation exists between the quality standards of nursing care and user satisfaction, was performed correlational quantitative study with transversal descriptive method-prospective. We worked with a sample of 140 users puerperal women hospitalized in the Gynecology- Obstetrics Service of Belen Hospital of Trujillo, the same that met the inclusion criteria proposed. Based on the theory of Donabedian (1984 and 1995), two instruments were applied: "Standards of Nursing Care Quality" and "Questionnaire of User Satisfaction Study" through observation and interview techniques, respectively. It was determined that: a)highly significant statistical relation exists between the quality standards of care and user satisfaction (p < 0.000); b) The quality standards of nursing care were by 81% adequate, and inadequate by 19%, users chosen for this study were satisfied by 87% and 13% were dissatisfied. c) There is no significant relation exists (p> 0.05) between the standard of technical quality of nursing care and user satisfaction from the technical dimension, or between the human quality standard of nursing care and user satisfaction from the interpersonal dimension; d) the quality standard of the work environment of nursing care and user satisfaction from the comfort dimension significantly related (p<0.05). Keywords: Standards, Quality, Care Nursing, Satisfaction and User.